GREETING WITH A HOLY KISS: A STUDY OF 1 THESSALONIANS 5:26 IN SOME GHANAIAN MOTHERTONGUE TRANSLATIONS OF THE BIBLE - Kuwornu-Adjaottor, Jonathan E. T. (European Scientific Journal, ESJ, 2014)
There seem to be translation and interpretation challenges facing mother-tongue readers of the Bible in their cultural settings. One of such cultural issues is the translation of 1Thess 5:26 in some Ghanaian mother-tongue Bibles which borders on the mode of greeting among Christians. This paper is a study of the 1 Thess 5:26 in the Greek New Testament and 20 Ghanaian mother-tongue translations of the text in six southern Ghanaian languages. The paper argues that greeting with a “holy kiss,” in 1Thess 5:26 which most of the Ghanaian mother-tongue translations seem to promote is not Ghana/African, and thus the verse should be retranslated to reflect Ghanaian culture.